CG4928 Is Vital for Renal Function in Fruit Flies and Membrane Potential in Cells: A First In-Depth Characterization of the Putative Solute Carrier UNC93A - Ceder, Mikaela M.; Aggarwal, Tanya; Hosseini, Kimia; Maturi, Varun; Patil, Sourabh; Perland, Emelie; Williams, Michael J.; Fredriksson, Robert (Frontiers in Cell and Developmental Biology, 2020)
The number of transporter proteins that are not fully characterized is immense. Here, we used Drosophila melanogaster and human cell lines to perform a first in-depth characterization of CG4928, an ortholog to the human UNC93A, of which little is known. Solute carriers regulate and maintain biochemical pathways important for the body, and malfunctioning transport is associated with multiple diseases. Based on phylogenetic analysis, CG4928 is closely related to human UNC93A and has a secondary and a tertiary protein structure and folding similar to major facilitator superfamily transporters. Ubiquitous knockdown of CG4928 causes flies to have a reduced secretion rate from the Malpighian tubules; altering potassium content in the body and in the Malpighian tubules, homologous to the renal system; and results in the development of edema. The edema could be rescued by using amiloride, a common diuretic, and by maintaining the flies on ion-free diets. CG4928-overexpressing cells did not facilitate the transport of sugars and amino acids; however, proximity ligation assay revealed that CG4928 co-localized with TASK1 channels. Overexpression of CG4928 resulted in induced apoptosis and cytotoxicity, which could be restored when cells were kept in high-sodium media. Furthermore, the basal membrane potential was observed to be disrupted. Taken together, the results indicate that CG4928 is of importance for generating the cellular membrane potential by an unknown manner. However, we speculate that it most likely acts as a regulator or transporter of potassium flows over the membrane.